How Collective Bargaining Shapes Poverty: New Evidence for Developed Countries - Kevin Pineda-Hernández; Francois Rycx; Mélanie Volral (Institute of Labor Economics (IZA), 2021)
Although many studies point to the significant influence of collective bargaining institutions on earnings inequalities, evidence on how these institutions shape poverty rates across developed economies remains surprisingly scarce. It would be a mistake, though, to believe that the relationship between earnings inequalities and poverty is straightforward. Indeed, whereas earnings inequalities are measured at the individual level, poverty is calculated at the household level using equivalised (disposable) incomes. Accordingly, in most developed countries poverty is not primarily an issue of the working poor. This paper explicitly addresses the relationship between collective bargaining systems and working-age poverty rates in 24 developed countries over the period 1990-2015. Using an up-to-date and fine-grained taxonomy of bargaining systems and relying on state-of-the-art panel data estimation techniques, we find that countries with more centralised and/or coordinated bargaining systems display significantly lower working-age poverty rates than countries with largely or fully decentralised systems. However, this result only holds in a post-tax benefit scenario. Controlling for country-fixed effects and endogeneity, our estimates indeed suggest that the poverty-reducing effect of collective bargaining institutions stems from the political strength of trade unions in promoting public social spending rather than from any direct effect on earnings inequalities.
Keywords: C23; C26; I32; I38; J51; J52; 330; collective bargaining systems; poverty rates; social security expenditures; panel data; advanced economies